Quality of Life of Elderly People Living in Different Types of Long-term Care Facilities - Cíntia Aparecida Anjos; Mirna Clemente; Josiane de Fátima Gaspari Dias; Ligia Moura Burci; Rômulo de Oliveira Leite; Marilis Dallarmi Miguel (Universidade de São Paulo, 2022)
Abstract Population aging is a worldwide occurrence that has become urgent in developing countries. Quality of life can be measured to identify functional capacity and determine the degree of impact on quality of life exerted on an individual. This study aimed to measure the quality of life of elderly people who have been living in different long-term care facilities for the elderly. Therefore, this research was developed with a qualitative and descriptive approach. Data were obtained from medical records and interviews, and were analyzed in R language interpreter software on the Ubuntu Linux operating system. Seventy-nine elderly people participated in the study. Eleven lived in Home Marista, and 68 lived in Home Jesus Maria José. A socioeconomic questionnaire was used to collect data on the socioeconomic characteristics of the participants. The Mini-Mental State Exam was used to measure degree of cognition. The Short Form-36 Questionnaire was used to measure quality of life. The present study suggests that the results found can clarify the individual vulnerability of the elderly in the age group studied regardless of the type of residence. Despite the discrepancy found regarding the care provided at the long-term care facilities, the scores, obtained with the quality of life assessment, did not show significant differences.